UJI TOKSISITAS PELEMBUT PAKAIAN TERHADAP BENIH IKAN MAS (Cyprinus carpio L.) Fabric Softener Toxicity Test Against Goldfish Seed (Cyprinus carpio L.) - Shusi Novita Siregar; Irwanmay Irwanmay; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Solution of fabric softener contained cationic surfactant by type quaternary ammonium chloride compounds that harm aquatic life and the environment led to the death of fish. This reaserch intend to determine the level of attack power and influence of fabric softener toxicity to carp seed, this research was conducted on July − November 2013 in the Department of Agriculture and Marine Medan. Stages of testing include : a preliminary test, a definitive test to determine the LC50 until 96 hours and sublethal tests with various concentrations. The results showed of the preliminary test studies have upper threshold value ( N ) of 100 ppm and below the threshold value ( n ) 75 ppm. Test results obtained definitive 96 hour LC50 value of 87.10 ppm. The test results on the highest survival sublethal concentration of 2.61 ppm treatment that is equal to 80 % while the lowest survival at 7.84 ppm concentration and 46.66 %, the highest feed efficiency at treatment concentrations of 2.61 ppm is equal to 4.98 % and the lowest in the treatment of 1.55 % 7.84, and the highest growth rate in the treatment concentration of 2.61 ppm is 0.15 % while the lowest at treatment concentrations of 7.84 ppm at 0.05%. Water quality parameters were observed during the definitive test decreased DO 2.0 − 6.4 mg / l, the temperature increased 27.1 − 30.20C and pH decrease during each treatment concentration of 3 − 6.6 . Water quality parameters at sublethal test that does not decrease drastically DO range 5.2 − 7.6 mg/l, temperature range 27 − 290C and a pH range of 3.4 − 7.5 .Keywords : Fabric Softener, Cyprinus carpio L., toxicity